Blast control and nitrogen management in lowland rice cultivation - Fageria, Nand Kumar; Prabhu, Anne Sitarama (Pesquisa Agropecuaria Brasileira, 2004)
Nitrogen timing and control of fungal diseases are cultural practices in lowland rice production. The objective of this study was to determine appropriate timing of N application and adequate rate of seed treatment with pyroquilon fungicide in lowland rice. The 90 kg ha-1 N application timing were alloted as follows: total at sowing (T1); 1/3 at sowing, 1/3 at active tillering and 1/3 at panicle initiation (T2); 1/2 at sowing and 1/2 at active tillering (T3); 1/2 at sowing and 1/2 at panicle initiation (T4); 2/3 at sowing and 1/3 at active tillering (T5); 2/3 at sowing and 1/3 at panicle initiation (T6); and 1/3 at sowing and 2/3 at the start of tillering (T7). Fungicide treatments were 0, 200, and 400 g active ingredient pyroquilon per 100 kg seed. Grain yield was significantly affected with timing of N application and fungicide treatments. Nitrogen treatment also affected significantly straw yield, and N uptake in grain. Maximum grain yield was obtained with treatments T2 and T3. Fungicide treatment of 200 g per100 kg of seed, produced significantly higher yield as compared to the control.